UTILIZATION OF FLY ASH AS MATERIAL MIXED SOIL LAYER BASICS IN HIGHWAY CONSTRUCTION - Rina Aulia; Yasruddin Yasruddin (CERUCUK, 2017)
The use of coal-fired electricity generation and industries including the unit Asphalt Mixing Plant (AMP) coal ash waste leaving the lot and become a problem for the environment. Utilization of coal waste is done in a variety of purposes including for construction, namely a mixture of base soil layer in road construction.The purpose of this study to determine the value of the characteristics of each combination of soil, cement and fly ash as a mixture of soil layer base with the composition of the mixture of 1 fly ash 25%, cement 15%, soil 60%, a mixture of 2 fly ash 30%, cement 10%, 60% land, and the mixture 3 35% fly ash, cement 5%, 60% land. The testing is done is test Atterberg limits, the specific gravity hydrometer, sieving, compacting and CBR.From the results of the third study variations in the mixture obtained value of the CBR highest in the combination of fly Ash 1 was 54%, which exceeds the value of the common specifications are a minimum of 6% as a heap of unusual, but the value of active obtained from the three test objects, none of which meet the specification of <1:25. So the combination of fly ash 1, 2, and 3 can be used as embankment usual with the terms of materials used only on the bottom of the heap or on the backfilling that does not require carrying capacity or strength of the shear is high, besides the material can only be used above 30 cm from the ground water level or the layer directly below the bottom of the pavement or road shoulder or shoulder of the road subgrade. Keywords: Fly Ash, Soil Characteristics Basic Specifications of Highways.